CGIAR Initiative to help develop low-emission food systems, key to meeting global climate targets - Verchot, Louis V.; Zhang, Wei (CGIAR System Organization, 2022)
The CGIAR Research Initiative on Low-Emission Food Systems, Mitigate+, will help low- and middle-income countries reduce food systems emissions without impeding progress toward development goals. With a food systems approach to cutting greenhouse gas emissions, this work could lead to a reduction in global emissions by 2 percent in 10 years.